(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Materialist ecofeminism is based on the assertion that sex gender inequality represents a material relation of inequality between dominant men and subordinate women. Ecofeminists view the dominant stream of modern science as a projection of Western men’s values. The privilege of determining what is considered scientific knowledge has been controlled by men. But for science, knowledge is attained through empirical evidence, and gender is not a concern at all. It is the population growth that drives the intensity of agricultural production and the resulting environmental issues. We survive with the help of science and we need science to survive. Science is not meant to oppress nature and thus oppress woman. Rather it is a rational route to resolve issues and move on.